2018
DOI: 10.2967/jnumed.118.207845
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Cholecystokinin-2 Receptor with the Minigastrin Analog 177Lu-DOTA-PP-F11N: Does the Use of Protease Inhibitors Further Improve In Vivo Distribution?

Abstract: Patients with metastatic medullary thyroid cancer (MTC) have limited systemic treatment options. The use of radiolabeled gastrin analogs targeting the cholecystokinin-2 receptor (CCK2R) is an attractive approach. However, their therapeutic efficacy is presumably decreased by their enzymatic degradation in vivo. We aimed to investigate whether the chemically stabilized analog Lu-DOTA-PP-F11N (Lu-DOTA-(DGlu)6-Ala-Tyr-Gly-Trp-Nle-Asp-Phe-NH2) performs better than reference analogs with varying in vivo stability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 23 publications
2
64
2
Order By: Relevance
“…The evaluation of the different radiolabeled minigastrin derivatives differing in both, the Cterminal peptide binding moiety and the structural characteristics of the linker, revealed that the compounds with six D-glutamic acid residues within the amino acid chain belong to the most promising substances with an reasonable balance of tumor uptake and decreased kidney reabsorption (11,12,16). The pronounced hydrophilicity of such compounds is most likely the reason for the fast renal excretion and shorter blood half-life of 177 Lu-PP-F11N in comparison to…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of the different radiolabeled minigastrin derivatives differing in both, the Cterminal peptide binding moiety and the structural characteristics of the linker, revealed that the compounds with six D-glutamic acid residues within the amino acid chain belong to the most promising substances with an reasonable balance of tumor uptake and decreased kidney reabsorption (11,12,16). The pronounced hydrophilicity of such compounds is most likely the reason for the fast renal excretion and shorter blood half-life of 177 Lu-PP-F11N in comparison to…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to reduce nephrotoxicity is to modify the compound itself: Amino acid chains with more than 5 glutamic acids in their sequence play an important role in the kidney reuptake mechanism and may reduce kidney uptake (10,11). Such an approach was implemented by several groups and resulted in the development of a library of improved radiolabeled minigastrin analogues (12)(13)(14)(15)(16)(17). Some of these new compounds show higher tumor uptake, higher tumor-to-kidney uptake ratios and higher serum stability, compared to the previously developed minigastrin analogues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already in 2002, [ 90 Y]Y-DTPA-MG0 was studied in 8 patients [234] with limited therapeutic success and severe nephrotoxic side effects, a reason why this study was not continued. Recently, pharmacokinetic properties, dosimetry, and the targeting ability of [ 177 Lu]Lu-DOTA-PP-F11N was tested in an initial clinical study for potential use of CCK2 receptor-based endoradiotherapy [235]. Tumour uptake seems sufficient for successful therapeutic use, with the stomach as the main dose-limiting organ.…”
Section: Other Target Structures Expressed On Tumour Cellsmentioning
confidence: 99%
“…PRRT with radiolabeled gastrin analogs is therefore an attractive treatment option for patients with recurrent or metastatic medullary thyroid cancer. Of large libraries, the analogs 177 Lu-PP-F11N (Table 2) and 111 In-CP04 (PP-F11, Table 2), as a surrogate for 177 Lu-or 90 Y-labeled CP04, are currently in early prospective trials (LUMED/ NCT02088645 and GRAN-T-MTC/NCT03246659, respectively) to determine safety, maximum tolerated dose, biodistribution, and dosimetry (24,25). Preliminary clinical data identified the stomach as a potential dose-limiting organ, whereas the renal absorbed dose was rather low.…”
Section: Gastrin In Medullary Thyroid Cancermentioning
confidence: 99%